Evaluation of Potential Attractants for Liposcelis bostrychophila (Psocoptera: Liposcelididae). Issue 2 (13th September 2014) - Diaz-Montano, John; Campbell, James F.; Phillips, Thomas W.; Throne, James E.
Abstract : The psocid, Liposcelis bostrychophila Badonnel (Psocoptera: Liposcelididae), can cause significant damage to stored commodities, and its pest status in the United States has been increasing over the last decade. Because L. bostrychophila is difficult to control with conventional methods, it is critical to explore alternative approaches such as the use of attractants that can be incorporated into integrated pest management programs for monitoring psocids. The orientation response of several L. bostrychophila life stages (first and second instars, third and fourth instars, 0- to 7-d-old adults, 21- to 28-d-old adults, and adults of mixed ages) to a range of potential attractants (including whole and cracked grains, grain-based oils, wheat germ, brewer's yeast, and commercially available kairomone lures) was studied using a two-choice pitfall test to identify candidates for further development as lures in traps. Among the potential attractants evaluated, the strongest response by all stages of L. bostrychophila was to brewer's yeast. Other materials for which there was consistently a strong response were psocid diet, wheat germ, and wheat germ oil. These results show the potential for developing monitoring tools for integrated pest management programs for L. bostrychophila and other psocid species.